Desain Adiktif dalam Platform Digital: Perspektif Hukum Perlindungan Konsumen dan Pembelajaran dari Uni Eropa - Ayu Galuh Anggraini (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Addictive design occurs when consumers are treated as assets whose behavior can be monetized. Although this issue has begun to be regulated, particularly in the European Union, consumer protection law in Indonesia still focuses on prohibiting misleading information. This study aims to analyze whether this practice can be categorized as a violation of consumer rights under the Consumer Protection Law (UUPK). The results indicate that addictive design has the potential to cause non-material losses not covered by the UUPK and a broader understanding of the principle of good faith by business actors on platforms is needed, as well as recognition of consumer behavioral manipulation as a form of prohibited conduct to strengthen consumer protection.